Hybrid gamma 2b-gamma 2a genes expressed in myeloma variants: evidence for homologous recombination. - Tilley, S A (1983)
The expressed immunoglobulin heavy chain genes of five gamma 2b-gamma 2a hybrid chain-producing variants of the mouse myeloma MPC-11 (gamma 2b, kappa) have been characterized by genomic Southern blot analysis. Results show that a hybrid gamma 2b-gamma 2a gene was formed in each variant by recombination between the expressed gamma 2b gene of MPC-11 and a gamma 2a gene. The recombination sites are within regions of marked homology between gamma 2b and gamma 2a genes: at least three and probably four variants show gamma 2b-gamma 2a recombination within the heavy chain constant region 2 (CH2) domain, while the fifth has its recombination site between the penultimate nucleotide of CH1 and the eighth nucleotide of the hinge. An unexpected finding is that the hybrid heavy chain-producing variants fall into two subgroups based on their use of different gamma 2a gene forms in hybrid gene formation. This result leads to the speculation that either a tandem gamma 2a gene duplication was present in MPC-11 prior to variant generation or mitotic recombination between chromosomes occurred in the generation of one variant subgroup. The similarity of hybrid gene formation in MPC-11 variants to that apparently responsible for concerted evolution within multigene families and hybrid protein expression in various individuals is noted, and the possible relationship between hybrid gene formation and the heavy chain class switch is discussed.